Presenting financial statements according to BAS 1: a study on organization of ACNABIN chartered accountants - Morshed, Riyadh (BRAC University, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.